21st Century Welfare Provision is more than the "social insurance state": A reply to Paul Pierson - Anton Hemerijck (Universität Bremen, Zentrum für Sozialpolitik (ZeS), 2011)
This article reflects on the important lecture The Welfare State Over the Very Long Run, delivered by Paul Pierson, at the London School of Economics on 8 November 2010, on the occasion of the launch of Oxford Handbook of the Welfare State. Pierson's explanation for what he sees as the surprising stability of the welfare state over the past three to four decades of permanent austerity is largely rooted in fears of electoral ret-ribution and organized interest opposition against social reform (cf. Pierson 2011). While, in a nutshell, Pierson's lecture was a restatement of his famous new politics thesis with a nod to rival theoretical accounts, the present paper tries to go beyond Pierson's account of change-resistant welfare states by adding a number of empirical as-pects and theoretical dimensions to the debate on the long-term transformation of the welfare state. Empirically, on the one hand, the paper highlights several significant qualitative changes in social insurance provision, macroeconomic policy priorities, la-bor market policy and regulation, industrial relations, old age pension, social services and social policy administration, that are largely absent from Pierson's portrayal, also given his choice of data. The observation of profound social reform raises important theoretical issues for the comparative study of welfare state development. Here the pa-per points to underappreciated theoretical mechanisms, especially dynamics of policy learning in mature welfare state. In sum, the paper observes more profound change on the dependent variable requiring both a softening and updating of the theoretical biases to path-dependent institutional inertia. If policy makers, contrary to received wisdom, do engage in major reforms in spite of many institutional obstacles and negative political incentives, what distin-guishes these actors and the institutional conditions under which they operate, from the seemingly more general case of welfare inertia? In conclusion, the article argues that the readiness to use information feedback from past performance, new ideas and expertise and the inspiring reforms successes in many countries, should count as important con-duits or mechanisms explaining reforms. – – Dieser Artikel beschäftigt sich mit dem bedeutenden Vortrag The Welfare State Over the Very Long Run, den Paul Pierson anlässlich der Herausgabe des Oxford Handbook of the Welfare State am 8. November 2010 an der London School of Economics gehalten hat (vgl. Pierson 2011). Piersons Erklärung für die seiner Meinung nach bemerkenswerte Stabilität des Wohlfahrtsstaates in den von permanenter Austerität geprägten vergangenen drei bis vier Jahrzehnten basiert im Wesentlichen auf der Angst der politischen Eliten vor der Abstrafung an der Wahlurne und dem Widerstand organisierter Interessen gegen Sozialreformen. Vorliegender Aufsatz beleuchtet sowohl die empirischen als auch die theoretischen Grenzen dieser These eines wandlungsresistenten Wohlfahrtsstaates. In empirischer Hinsicht weist er auf eine nicht unerhebliche Anzahl von qualitativen Veränderungen hin, etwa auf der Ebene der Sozialversicherung, makroökonomischer Politikprioritäten, der Arbeitsmarktpolitik und -regulierung, der Beziehungen von Arbeitgebern und Arbeitnehmern, Renten, sozialen Dienstleistungen und der Sozialverwaltung. Die Beobachtung grundlegender Sozialreformen werfen wichtige theoretische Fragen für das vergleichende Studium wohlfahrtstaatlicher Entwicklung auf: Was unterscheidet politische Entscheidungsträger und die institutionellen Bedingungen, unter denen sie agieren, von dem anscheinend weitaus üblicheren Fall von Reformträgheit, wenn diese Akteure - entgegen der landläufigen Meinung - trotz einer Vielzahl institutioneller Hindernisse und negativer politischer Anreize umfassende Reformen anstoßen? Als Schlussfolgerung argumentiert dieser Aufsatz, dass die Lehren vergangener Performanz, neue Ideen und Expertisen sowie anregende Reformerfolge in vielen Ländern als wichtige Mechanismen gelten müssen, mit denen sich wohlfahrtstaatliche Veränderungen erklären lassen.
Keywords: 300